Role of Respiratory Epithelial Cells in Allergic Diseases - Constanze A. Jakwerth; Jose Ordovas-Montanes; Simon Blank; Carsten B. Schmidt-Weber; Ulrich M. Zissler (Cells, 2022)
The airway epithelium provides the first line of defense to the surrounding environment. However, dysfunctions of this physical barrier are frequently observed in allergic diseases, which are tightly connected with pro- or anti-inflammatory processes. When the epithelial cells are confronted with allergens or pathogens, specific response mechanisms are set in motion, which in homeostasis, lead to the elimination of the invaders and leave permanent traces on the respiratory epithelium. However, allergens can also cause damage in the sensitized organism, which can be ascribed to the excessive immune reactions. The tight interaction of epithelial cells of the upper and lower airways with local and systemic immune cells can leave an imprint that may mirror the pathophysiology. The interaction with effector T cells, along with the macrophages, play an important role in this response, as reflected in the gene expression profiles (transcriptomes) of the epithelial cells, as well as in the secretory pattern (secretomes). Further, the storage of information from past exposures as memories within discrete cell types may allow a tissue to inform and fundamentally alter its future responses. Recently, several lines of evidence have highlighted the contributions from myeloid cells, lymphoid cells, stromal cells, mast cells, and epithelial cells to the emerging concepts of inflammatory memory and trained immunity.